2003
DOI: 10.1128/jvi.77.12.6709-6719.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Avian Retroviral Host Range Extension

Abstract: Alpharetroviruses provide a useful system for the study of the molecular mechanisms of host range and receptor interaction. These viruses can be divided into subgroups based on diverse receptor usage due to variability within the two host range determining regions, hr1 and hr2, in their envelope glycoprotein SU (gp85). In previous work, our laboratory described selection from a subgroup B avian sarcoma-leukosis virus of an extended-host-range variant (LT/SI) with two adjacent amino acid substitutions in hr1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…The selection of resistance alleles to ASLVs may also be hampered by the ability of retroviruses to evolve the structure of their envelope glycoproteins to alter their receptor usage. A variety of studies have demonstrated that ASLV can acquire mutations that alter the envelope and the viral host range (24,25,31,34,43). Subgroups of highly related viruses that use different proteins as receptors may vary the selective pressure to make it difficult for chickens to develop complete resistance to ASLV entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of resistance alleles to ASLVs may also be hampered by the ability of retroviruses to evolve the structure of their envelope glycoproteins to alter their receptor usage. A variety of studies have demonstrated that ASLV can acquire mutations that alter the envelope and the viral host range (24,25,31,34,43). Subgroups of highly related viruses that use different proteins as receptors may vary the selective pressure to make it difficult for chickens to develop complete resistance to ASLV entry.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have developed strategies that mimic resistance to ASLV entry in cell culture to study the evolution of the envelope glycoprotein. These studies demonstrated that blocking virus entry could select viral variants with mutations in the viral glycoproteins that altered receptor usage (24,25,31,34,43). The goal of the present study was to identify and characterize the mutations in the subgroup A receptor in lines of chickens that cause resistance to infection by ASLVs carrying the subgroup A envelope glycoproteins.…”
mentioning
confidence: 99%
“…One strategy is likely via high-affinity binding between the viral glycoproteins and the receptors. In contrast, another strategy is that mutations in viral glycoproteins allow the infection of diverse host cells without an evident increase in receptor binding (20). In this report, we have shown large differences in viral entry between quail and chicken LDL-A modules for the mutant viruses Y142N, E149K, and Y142N/E149K (see Table 1), but we were unable to observe corresponding differences in binding between quail and chicken LDL-A with the mutant envelope proteins (data not shown).…”
mentioning
confidence: 99%
“…Subsequent accommodation of envelope proteins can result in complete changes of receptor usage and cellular tropism. Whereas escape mutants of ASLVs with expanded viral receptor usage were already selected on cocultivated permissive and nonpermissive cells (34,38) or exerted by the presence of soluble competitor Tva (27), the natural occurrence of receptor variants with decreased susceptibility to ASLV infection remains to be explored. As a proof of the principle, we have identified a singleamino-acid substitution in the Tvb receptor that results in reduced susceptibility to ASLV subgroups B and D and resistance to subgroup E (35).…”
mentioning
confidence: 99%